(3GddHGH aj eYQaI GdCfSGHs - (3Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO GdTjHGfqj GdLRQj, CHh GdMSf YR GdOjf GHf GdCKjQ , J (B630 (3g`s; (3YHO GdcQje Hf eMeO Hf efUhQ GdJejej GdSeYGfj GdeQhRj, CHh SYO,J (B562 (3g` s
(3ChdgG (B:s
(3jHOC HJQGLe MQa GdOGd GdegedI , hChdgG fSHI GdOGHhjj s
(3BNQgG (B:s
(3hjfJgj HfgGjI MQa GdZjf HJQLeI GdZjfj HaJM GdZjf GdoeYLeI hGdjGA GdJMJjI hHYOgG dGe Cda Ke fhf s
(3fSNI SGOSIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B4s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B354 s
Keywords: (3GdJGQjNs